Functional design of biker jacket finishing elements with the use of ecological materials - Pustiulha, Serhiy; Golovachuk, Ihor; Samchuk, Volodymyr; Shenderuk, Polina (Theory and practice of design, 2022)
The paper presents the results of development and implementation of the basic principles of functional design of finishing elements for biker clothes with the use of environmentally friendly materials. The aim of the work is to analyze the modern design of biker jackets as one of the main biker attributes, as well as to develop and implement basic principles of functional design of finishing elements for biker clothes using environmental materials. The object of research is a biker jacket — “koshuha”. The subject of research is the functional design of finishing elements, which can be performed with the involvement of environmental materials. The functionality of biker jackets, as the main element of biker clothing, is classified according to two parameters: efficiency and physiology. Signs of the cost-effectiveness of a biker jacket are its durability and practicality. Indicators of the economic functionality of “koshuh” are: its dark, unbranded colors, their use in the manufacture of genuine leather. The physiological functionality of a biker jacket means its convenience and comfort. Indicators of physiological functionality of the jacket include indicators, the main of which are: the ability not to restrict the movements of the owner, well protect him from bad weather, the presence of functional pockets, and the presence of reinforcement with unique security features. Each of the biker “coats”, having functional and decorative components, in different situations can perform both the function of convenience and comfort and be deprived of any functionality. Therefore, concepts such as functionality and individual decoration of biker jackets are theoretically situational characteristics. A historical excursion of the stages of formation of the philosophy of the biker movement is made. The analysis of approaches to the modern design of a biker jacket as one of the main biker attributes is carried out. A number of features that distinguish the biker jacket from its standard variants are highlighted. Factors influencing the functional characteristics of biker outerwear are analyzed. The influence of elements of individual decoration of biker jackets on their safety properties is considered. Based on the analysis, the basic principles of optimizing the design of biker jackets “kosukh” are formed. Approaches to improving the design of individual finishing elements for biker clothes with the use of environmentally friendly materials have been developed and implemented.